Perancangan Perforasi Unik Pada Kemasan Botol Minuman Melalui Pendekatan User-Centered Design - Qonita, Syidda; Kamal, Dianta Mustofa; Kusumantoro, Heribertus Rudi (Fakultas Teknik Universitas Tulang Bawang, 2026)
Innovation Innovations in beverage packaging design currently focus on enhancing user experience, sustainability, and brand identity. However, conventional beverage packaging often fails to fully meet the needs for ease of opening, visual appeal, and new experiences sought by users, particularly younger consumers. Additionally, technical elements such as perforations have not been optimally utilized to enhance product interaction and aesthetic value. Therefore, this research is necessary to address these issues. Through a User-Centered Design (UCD) approach, this study identifies the needs and preferences of young users in the Jakarta metropolitan area, particularly in terms of ease of opening, visual appeal, and the new experiences offered. The design process began with a needs survey, followed by the development of a banana beverage bottle prototype incorporating a perforation system resembling the process of peeling a banana. An evaluation using the User Experience Questionnaire (UEQ) with 70 respondents revealed that all measured aspects—attractiveness, clarity, efficiency, accuracy, stimulation, and novelty—received positive impressions. These results confirm the effectiveness of UCD in producing innovative, user-friendly packaging designs that align with user expectations. Keywords: Bottle Packaging, Innovation, Perforation, UCD, User Experience (UX)